PERANCANGAN APLIKASI MOBILE EDUKATIF ‘BELAJAR CHORD GITAR UNTUK PEMULA’ BERBASIS ANDROID - Fitriyani, Aulia; Putri, Riana Defi Mahadji (Edu Komputika Journal, 2017)
Music is a Voices arrangement in such a way, so it has a tone, rhythm and harmony, especially the resulting sound of musical instruments. The guitar is a most popular musical instrument. learning guitar takes time and cost a lot. As previously with Technology developments, be required a Learning Media is moving. Therefore, The Writer design a guitar chord Learning Media Applications based android because android Operating System is a developing rapidly and many people have it. The purpose of research is to produce mobile application education 'learn the guitar chords for Beginners' Based android.The methods used to build this software is a waterfall, consists of analysis, design, implementation, and testing. Testing process Software is Framework validation. Testing process consists of black-box testing, material testing, and media testing.The results is a Mobile Application Education 'Learning Chord Guitar for Beginners' Based Android. Features From Application is Introduction Parts of the guitar, the techniques playing guitar, introduction of a guitar chord, guitar tuner, chord mayor and minor with tones, video examples chord songs, and chord songs examples. The result of Black-box testing show that functions Application is good, while the materials testing and media testing , learning guitar chords application shows the percentage of Eligibility Application respectively 91.32% and 87.15%, which means that the findings Of Process the validation included category Very decent OR Very Good. Suggestions for a review of research is 1) the must be user testing to review how the applications is effective or not, 2) USE evaluation questions, 3) USE streaming video Database until size of the application is NOT too big and can to publish video more, 4) improvement tuner features.